Pengaruh Aktifitas Fisik (Pemijatan) Terhadap Penurunan Tekanan Darah pada Lansia Yang Mengalami Hipertensi di PSTW “Meci Angi” Kota Bima - Chandra Irawan; Musmuliadin Musmuliadin; Eka Rudy Purwana; Ade Saputra (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Hypertension is one of the major health problems frequently experienced by the elderly and can lead to serious complications if not properly managed. Simple physical activities such as massage can serve as a non-pharmacological intervention to help reduce blood pressure. This study aimed to determine the effect of physical activity in the form of massage on reducing blood pressure in elderly individuals with hypertension at PSTW "Meci Angi" in Bima City. This research employed a quasi-experimental design with a pre-post test control group design. The sample consisted of 20 elderly people divided into two groups, an experimental group and a control group, with 10 respondents in each group. Data were collected using an observation sheet to measure blood pressure before and after the intervention. The t-test analysis showed a significance value (2-tailed) of 0.009, which was less than α = 0.05, indicating a significant effect of physical activity on lowering blood pressure among the elderly. Therefore, massage as a simple form of physical activity can be considered an alternative intervention in managing hypertension among the elderly in social care institutions.